2016
DOI: 10.1002/jsfa.7890
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation dose and plant density affect the volatile composition and sensory quality of dill (Anethum graveolensL.)

Abstract: The final recommendation is to use the irrigation dose ID2 and the plant density PD2 if the objective is to produce dill samples with the highest aromatic and sensory quality; however, if the only objective is to produce high amounts of dill, the best options are ID0 and PD0. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…The chromatographic set up and conditions were identical to those reported recently, with the only exception that the column used was a Restek Rxi‐1301 Sil MS (Restek Corporation, Palo Alto, CA, USA) with an internal diameter of 30 m × 0.25 mm and a film thickness of 0.25 μm.…”
Section: Methodsmentioning
confidence: 99%
“…The chromatographic set up and conditions were identical to those reported recently, with the only exception that the column used was a Restek Rxi‐1301 Sil MS (Restek Corporation, Palo Alto, CA, USA) with an internal diameter of 30 m × 0.25 mm and a film thickness of 0.25 μm.…”
Section: Methodsmentioning
confidence: 99%
“…Sowing density is important as plants grown under high-density (HD) conditions compete with each other for water, nutrition, and light, which often leads to changes in plant size, biomass, morphology, and productivity ( Hecht et al, 2016 ). Research about plant density refers to productivity, organ development, nutrition absorption, water heterogeneity, shade avoidance, and flowering ( Lemaire et al, 2005 ; Hagiwara et al, 2010 ; Li et al, 2011 , 2016 ; El-Zaeddi et al, 2016 ; Roig-Villanova and Martinez-Garcia, 2016 ; Song et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Shoot nitrogen (N) dynamics analysis in lucerne showed that N accumulation was less rapid when plant density was high, which was caused by a decrease in leaf biomass ( Lemaire et al, 2005 ). Additionally, plant density influences the volatile compositions of dill, suggesting differences in nutrient absorption at various densities ( El-Zaeddi et al, 2016 ). The effects of water supply heterogeneity on Perilla frutescens were greater at higher density than at lower density, indicating that competition for water makes plants more sensitive to water heterogeneity ( Hagiwara et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…In another paper, El-Zaeddi et al, (2017) determined that a later harvest date yielded more essential oil from dill. They also discovered that the highest sensory quality dill plants were grown at a density of 5.56 per meter with a higher than normal irrigation dose of 2180 m 3 /ha .…”
Section: Dillmentioning
confidence: 99%
“…Using both GC-EN and sensory analysis will set this study apart as a resource for farmers, food scientists, horticulturalists, and engineers. Herbs have been analyzed by gas chromatography (GC) and electronic nose (eNose) instruments on multiple occasions, but this study appears to be the first opportunity for basil, parsley or dill to be analyzed on a GC-EN instrument (Callan, Johnson, Westcott, & Welty ,1991;Masanetz & Grosch, 1998;Yousif, Scaman, Durance, & Girard, 1999;Díaz-Maroto, Pérez-Coello, & Cabezudo, 2002;Chang, Alderson, Hollowood, Hewson, & Wright, 2007;Calín-Sánchez, Lech, Szumny, Figiel, & Carbonell-Barrachina, 2012;Ghasemi Pirbalouti, Mahdad, & Craker, 2013;Weisany, Raei, & Pertot, 2015;Carvalho, Schwieterman, Abrahan, Colquhoun, & Folta, 2016;El-Zaeddi, Calín-Sánchez, Martínez-Tomé, Noguera-Artiaga, Burló, & Carbonell-Barrachina, 2016;El-Zaeddi, Martínez-Tomé, Calín-Sánchez, Burló, Carbonell-Barrachina, & Buettner, 2016;El-Zaeddi, Martínez-Tomé, Calín-Sánchez, & Burló, 2017).…”
Section: Chapter 1 Introductionmentioning
confidence: 99%